USE OF MODIFIED BITUMEN ROAD EMULSION IN THE CONSTRUCTION AND REPAIR OF ROADS (International journal of artificial intelligence, 2025)
This article highlights the effectiveness of using modified bituminous road emulsions in the construction and repair of roads, their physicochemical properties, and practical significance. Ways to improve the composition of bitumen emulsions by physicochemical modification, as well as the influence of polymer additives on the adhesion and elastic properties of bitumen, were studied. Based on the research results, it has been proven that the use of modified emulsions increases the service life of road surfaces and provides economic efficiency.